Unraveling the adaptive strategies of Mycoplasma hominis through proteogenomic profiling of clinical isolates - Pobeguts, Olga V.; Galaymina, Maria A.; Sikamov, Kirill V.; Urazaeva, Diana R.; Avshalumov, Alexander S.; Mikhailycheva, Maria V.; Babenko, Vlad V.; Smirnov, Igor P.; Gorbachev, Alexey Yu. (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Mycoplasma hominis (M. hominis) belongs to the class Mollicutes, characterized by a very small genome size, reduction of metabolic pathways, including transcription factors, and the absence of a cell wall. Despite this, they adapt well not only to specific niches within the host organism but can also spread throughout the body, colonizing various organs and tissues. The adaptation mechanisms of M. hominis, as well as their regulatory pathways, are poorly understood. It is known that, when adapting to adverse conditions, Mycoplasmas can undergo phenotypic switches that may persist for several generations. Methods To investigate the adaptive properties of M. hominis related to survival in the host, we conducted a comparative phenotypic and proteogenomic analysis of eight clinical isolates of M. hominis obtained from patients with urogenital infections and the laboratory strain H-34. Results We have shown that clinical isolates differ in phenotypic features from the laboratory strain, form biofilms more effectively and show resistance to ofloxacin. The comparative proteogenomic analysis revealed that, unlike the laboratory strain, the clinical isolates possess several features related to stress survival: they switch carbon metabolism, activating the energetically least advantageous pathway of nucleoside utilization, which allows slowing down cellular processes and transitioning to a starvation state; they reconfigure the repertoire of membrane proteins; they have integrative conjugative elements in their genomes, which are key mediators of horizontal gene transfer. The upregulation of the methylating subunit of the restriction-modification (RM) system type I and the additional components of RM systems found in clinical isolates suggest that DNA methylation may play a role in regulating the adaptation mechanisms of M. hominis in the host organism. It has been shown that based on the proteogenomic profile, namely the genome sequence, protein content, composition of the RM systems and additional subunits HsdM, HsdS and HsdR, composition and number of transposable elements, as well as the sequence of the main variable antigen Vaa, we can divide clinical isolates into two phenotypes: typical colonies (TC), which have a high growth rate, and atypical (aTC) mini-colonies, which have a slow growth rate and exhibit properties similar to persisters. Discussion We believe that the key mechanism of adaptation of M. hominis in the host is phenotypic restructuring, leading to a slowing down cellular processes and the formation of small atypical colonies. This is due to a switch in carbon metabolism and activation the pathway of nucleoside utilization. We hypothesize that DNA methylation may play a role in regulating this switch.